Strategi Pengembangan Ekonomi Kreatif Mendukung Daya Saing Daerah Kota Tangerang - Swastuti, Endang; Pudjiarti, Emiliana Sri (JPAP: Jurnal Penelitian Administrasi Publik, 2021)
The development of the creative economy is in the context of overcoming the problems and challenges of regional economic development and reducing the dependence of the national economy on the extraction of natural resources (mining, minerals and plantations), the problem of poverty. There are 16 types of creative economy in the city of Tangerang, namely: Fine arts; Architecture; Games & developer applications; Publishing; Performing Arts; Visual communication design; Craft; Film, Animation and Video; Photography; Product Design; Television & radio; Culinary; Advertising; Music; Fashion and Interior Design. The existence of all creative economic activities in one regional locality shows the growing spirit of the local economy and the quantity of demand. Within the conceptual framework of strategic needs, there are 3 (three) things that must be considered in the creative economy development of Tangerang City, namely: (1) locality characteristics, (2) micro-meso-macro level performance, and (3) demand factors, technological factors, tourism factor.